Attitudes of Out-of-School Youths towards Tree Planting Activities in Central Uganda: A Case Study of Masaka District - Agea, Jacob G.; Nansereko, Susan; Obua, Joseph; Waiswa, Daniel; Buyinza, Mukadasi; Yikii, Fred (Academy Science Publishers, 2009)
This study assessed the attitudes of out-of-school youths towards tree planting activities in Masaka district, central Uganda. Data were collected using 104 semi-structured questionnaires. Logistic regression was used to show the influence of demographic and socio-economic characteristics of the respondents on their attitudes towards tree planting. Summative attitudes index varied from 320 for those who liked very much tree planting activities to 6 for those who disliked very much tree planting activities. Opinions on willingness to plant and tender trees also varied widely from summative index of 305 for those who would very much plant and manage the trees to 5 for those who would very much not plant and manage the trees. Sex, age, education, occupation, distance to the nearest trading centre and land ownership significantly contributed to variation in the attitudes. Factors such as lack of capital; land and tree tenure security; long payback period from planted trees; bad beliefs, taboos and superstitions about certain trees hindered out-of-school youths’ efforts. There is a need to develop clear policies and by-laws to guide and induce the out-of-school youths to plant trees as a livelihood opportunity.
Keywords: Youths; School dropouts; Tree planting; Forestry; Uganda